The sense of mineness in personal memory: problems for the endorsement model - Trakas, Marina (Estudios de Filosofía, 2021)
What does it take for a subject to experience a personal memory as being her own? According to Fernández’ (2019) model of endorsement, this particular phenomenal quality of our memories, their “sense of mineness”, can be explained in terms of the experience of the mnemonic content as veridical. In this article, I criticize this model for two reasons: (a) the evidence that is used by Fernández to ground his theoretical proposal is dubious; and more importantly, (b) the endorsement model does not accommodate many non-pathological everyday memories that preserve their sense of mineness, but whose veridicality is explicitly denied, suspected, not automatically endorsed, or neither denied nor endorsed. Finally, I sketch two alternative explanations: one also problematic, the other one more promising, and present some normative advantages of the latter. This also displays the undesirability of the endorsement model from a normative perspective.